THE IDEOLOGIZATION OF MUSIC IN THE STALINIST ERA - Lois Paula VĂDUVA (Studia Universitatis Babeş-Bolyai. Musica, 2022)
In the XXth century, the world witnessed some of the cruellest totalitarian regimes in history. In this time, the Soviet Union was confronted with the leadership of Stalin that proved to be much more dangerous that the one of his predecessor. The musical world was not exempt from the ideology promoted and imposed by Stalin and the Communist Party. Music had to be composed under the auspices of social realism and composers that refused to align themselves with this ideology found themselves suffering severe consequences varying from the loss of their job to the very loss of their freedom and life. Given the severity of the Stalin’s regime, most musicians tried to publicly salute the communist ideology, but notably a number of composers started a path of resistance through clandestine music that was composed in accordance to their artistic values.